2005
DOI: 10.1002/ejoc.200400623
|View full text |Cite
|
Sign up to set email alerts
|

High‐Content Photochromic Polymers Based on Dithienylethenes

Abstract: Dithienylethenes (DTEs) are one of the most promising classes of photochromic compounds for use in optoelectronic devices such as waveguides, memory media and sensors. The development of DTE based polymers that contain a high mass-content of the photoactive DTE component, that maintain their photochromic activity in the solid-state and that are easily processed into thin-films under a variety of conditions is critical for the implementation of the materials into useful applications. This Microreview provides a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(44 citation statements)
references
References 36 publications
0
44
0
Order By: Relevance
“…Some examples of these stimuli include heat, [1][2][3][4][5][6][7][8][9] deformation, [10][11][12][13][14][15][16][17][18][19][20] chemicals, [21][22][23] light, [24][25][26] and others, [27,28] which make the sensors useful for a wide range of technologies. [29,30] We recently reported on a new class of polymers with built-in optical deformation [31][32][33][34][35] and threshold temperature [33,34,36] sensors.…”
Section: Introductionmentioning
confidence: 99%
“…Some examples of these stimuli include heat, [1][2][3][4][5][6][7][8][9] deformation, [10][11][12][13][14][15][16][17][18][19][20] chemicals, [21][22][23] light, [24][25][26] and others, [27,28] which make the sensors useful for a wide range of technologies. [29,30] We recently reported on a new class of polymers with built-in optical deformation [31][32][33][34][35] and threshold temperature [33,34,36] sensors.…”
Section: Introductionmentioning
confidence: 99%
“…To achieve such goals, we proposed backbone photochromic polymers, where the photochromic units are part of the polymer main chain [11][12][13]. In particular, it has been shown that polyurethanes are good candidates, showing good resistance to solvents and allowing for versatile polymerization and processing.…”
Section: Introductionmentioning
confidence: 99%
“…6.1.1.2 Reactions Involving Carbon-Carbon Bond Cleavage: Diarylethenes (DTEs), Fulgides, and Fulgimides The photogenerated isomers of diarylethenes (DTEs) and fulgides are thermally irreversible (P-type) and lend themselves to being very useful photochromic switches because they exhibit bistability and high quantum efficiencies for forward and reverse reactions [7,27,28]. DTEs exhibit better fatigue resistance and have higher durability than fulgides.…”
Section: Examples Of Photochromic Systemsmentioning
confidence: 99%